2015
DOI: 10.3926/jiem.1418
|View full text |Cite
|
Sign up to set email alerts
|

Post-vehicle-application lithium-ion battery remanufacturing, repurposing and recycling capacity: Modeling and analysis

Abstract: Abstract:Purpose: A mathematical model is used to help determine the manufacturing capacity needed to support post-vehicle-application remanufacturing, repurposing, and recycling of lithium-ion batteries over time. Simulation is used in solving the model to estimate capacity in kWh.Lithium-ion batteries that are commonly used in the electrification of vehicles cannot be simply discarded post-vehicle-application due to the materials of which they are composed. Eventually, each will fail to hold a charge and wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…The refurbishment process usually entails costly reengineering of an EV battery for a non-vehicle stationary storage application through battery disassembly, testing degradation and failure rates, repairing any damages, removal and replacement of substandard cells, reassembly of the module and pack, packaging for B2U application and adding electrical hardware, control and safety system (Derousseau et al 2017;Standridge & Hasan 2015;Foster et al 2014;Ahmadi et al 2014a;Cready et al 2003). Today, EV batteries consist of many components such as lithium-ion cells, battery management systems, sensors and cooling systems, which in principle can all be re-used in B2U concepts (Fischhaber et al, 2016).…”
Section: Figure 1 Life Cycle Of Electric Vehicle Batteries Considering Battery Second Usementioning
confidence: 99%
“…The refurbishment process usually entails costly reengineering of an EV battery for a non-vehicle stationary storage application through battery disassembly, testing degradation and failure rates, repairing any damages, removal and replacement of substandard cells, reassembly of the module and pack, packaging for B2U application and adding electrical hardware, control and safety system (Derousseau et al 2017;Standridge & Hasan 2015;Foster et al 2014;Ahmadi et al 2014a;Cready et al 2003). Today, EV batteries consist of many components such as lithium-ion cells, battery management systems, sensors and cooling systems, which in principle can all be re-used in B2U concepts (Fischhaber et al, 2016).…”
Section: Figure 1 Life Cycle Of Electric Vehicle Batteries Considering Battery Second Usementioning
confidence: 99%
“…To this end, three routes are considered in the literature. First, batteries that are still in good condition when an EV fails for other reasons could be reused for cars of the same brand [65] , especially after replacing damaged cells [66] . This would reduce demand for battery replacement (which in turn lowers demand for metals such as lithium, cobalt, nickel, manganese).…”
Section: Resultsmentioning
confidence: 99%
“…A cost-benefit analysis showed that remanufacturing a battery could save about 60% of the total cost of production of a new battery [293]. Moreover, it is estimated that a remanufacturing rate of 55% can lead to a reduction of the new batteries production needs in 10% [294].…”
Section: Remanufacturingmentioning
confidence: 99%